2008
DOI: 10.1080/02732170701796429
|View full text |Cite
|
Sign up to set email alerts
|

Black-White Differences in School Suspension: Effect of Student Beliefs About Teachers

Abstract: Research suggests that there are differences in the frequency with which white and African American students are punished in schools, with African American students being 2.3 times more likely to be suspended than white students. Most of the research on school punishment has focused on documenting race differences and looking for student and school-level factors to help explain disproportionality in out-of-school suspension. This study aims to fill the gap in the literature by analyzing the role of the teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 25 publications
(33 reference statements)
1
32
0
Order By: Relevance
“…2001). In addition, a recent study examining the relationship between student beliefs about teachers and likelihood of suspension found that students who believed that their teachers held high expectations for them had a significantly lower likelihood of in‐school and out‐of‐school suspension (Hinojosa 2008).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…2001). In addition, a recent study examining the relationship between student beliefs about teachers and likelihood of suspension found that students who believed that their teachers held high expectations for them had a significantly lower likelihood of in‐school and out‐of‐school suspension (Hinojosa 2008).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In her study focusing on teacher influence, Hallinan (2008) finds that students who believe their teachers care about them, respect them, and praise them are more likely to like school, which has been linked to lower incidents of deviant behavior (Dornbusch et al 2001). In addition, a recent study examining the relationship between student beliefs about teachers and likelihood of suspension found that students who believed that their teachers held high expectations for them had a significantly lower likelihood of in-school and out-of-school suspension (Hinojosa 2008).…”
Section: Authority In the Classroom And The Teacher-student Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, researchers have found that minorities are disproportionately represented in the administration of school discipline (for example, McCarthy and Hoge, 1987;McFadden and Marsh, 1992; Raffaele Mendez and Knoff, 2003;Skiba, Peterson, and Williams, 1997;Skiba et al, 2002;Thornton and Trent, 1988;Wooldridge and Richman, 1985;Wu et al, 1982). In addition, there is a substantial literature on the connection between the race of teachers and student performance, most notably regarding grades and test scores (for example, Bahr and Fuchs, 1991;Beady and Hansell, 1981;Dee, 2005;Ferguson, 1998;Goebes and Shore, 1975;Hinojosa, 2008;Prieto andZucker, 1981;Sheets, 1996;Taylor, Gunter, and Slate, 2001).…”
mentioning
confidence: 94%
“…Regarding problem behaviors, compared to White children, Black children are more likely to have school problems such as suspensions and dropouts (Brooks, Schiraldi & Ziedenberg, ; Hinojosa, ; Kena et al., ), to be homeless (Shah et al., ; Substance Abuse and Mental Health Services Administration, ), and to be arrested at higher rates (Chauhan, Fera, Welsh, Balazon & Misshula, ; Puzzanchera, ). Black children are also more likely to live in poorer and more disordered neighborhoods (Chauhan, Reppucci, Burnette & Reiner, ; Kelly, Schootman, Baker, Barnidge & Lemes, ).…”
Section: The Importance Of Racementioning
confidence: 99%